Task-Based Language Teaching in Indonesia: Overcoming Constraints for Effective Language Learning - Izzuddin; Mustain (Nusantara Journal of Multidisciplinary Science, 2024)
In Indonesia, English has been integrated into the educational system, yet it remains a foreign language with limited exposure outside the classroom, posing challenges to effective language acquisition. This study examines the feasibility of Task-Based Language Teaching (TBLT) as an alternative pedagogical approach in Indonesian classrooms to address these challenges. Utilizing a qualitative case study, this study analyzes teacher-student interactions and engagement during TBLT’s pre-task, task cycle, and language focus phases. The findings indicate that TBLT offers a balance between grammar instruction and communicative competence, making it a viable approach within Indonesia’s educational constraints. Anticipated challenges, such as class size, student reluctance, and curriculum alignment, can be mitigated through teacher training, the use of engaging tasks, and developed materials. This study suggests that TBLT, particularly its weak version, aligns well with the Indonesian context, where it has the potential to foster language skills while accommodating curriculum requirements